An update on the management of hepatitis C: guidelines for protease inhibitor-based triple therapy from the Latin American Association for the Study of the Liver - Chávez Tapia, Norberto C.; Ridruejo, Ezequiel; De Mattos, Angelo Alves; Bessone, Fernando; Daruich, Jorge; Sánchez Ávila, Juan F.; Cheinquer, Hugo; Zapata, Rodrigo; Uribe Esquivel, Misael; Bosques Padilla, Francisco Javier; Gadano, Adrián; Soza, Alejandro; et al. (2013)
Hepatitis C is a common cause of end-stage liver disease, and the main indication for liver transplantation in Latin America. Treatment of hepatitis C infected patients improves important long-term outcomes as mortality. Sustained viral response is reached in near 50% of patients with the previous management based in pegylated interferon and ribavirin. Recently new drugs were available increasing sustained viral response significantly, changing the standard of care to triple therapy. This guidelines provides a framework for practitioner in Latin America, to the management of patients with hepatitis C chronic infection.